2009
DOI: 10.1111/j.1537-2995.2009.02306.x
|View full text |Cite
|
Sign up to set email alerts
|

Genetically engineered pig red blood cells for clinical transfusion: initial in vitro studies

Abstract: GTKO RBCs were significantly more compatible than ABO-I and WT RBCs, but were not comparable to ABO-C combinations. In the presence of antibody, human monocyte-derived macrophages phagocytosed ABO-I RBC/sera combinations more efficiently than pRBCs. These observations contribute to our ultimate goal of using genetically engineered pRBCs for clinical blood transfusion. However, pigs will require other modifications or manipulations if they are to become suitable for human transfusion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
47
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 31 publications
(50 citation statements)
references
References 40 publications
3
47
0
Order By: Relevance
“…As our group has previously reported [23, 24], both Gal and Neu5Gc were expressed on wild-type pig RBCs and AECs, but hCD46 was not (Fig 1). RBCs and AECs from GTKO/CD46 pigs expressed Neu5Gc, but not Gal; the AECs expressed hCD46, but RBCs did not (as the transgene is not expressed in RBCs as they have no nuclei).…”
Section: Resultssupporting
confidence: 71%
See 1 more Smart Citation
“…As our group has previously reported [23, 24], both Gal and Neu5Gc were expressed on wild-type pig RBCs and AECs, but hCD46 was not (Fig 1). RBCs and AECs from GTKO/CD46 pigs expressed Neu5Gc, but not Gal; the AECs expressed hCD46, but RBCs did not (as the transgene is not expressed in RBCs as they have no nuclei).…”
Section: Resultssupporting
confidence: 71%
“…RBCs (which express carbohydrate antigens but do not express swine leukocyte antigens [SLA]) were isolated as previously described [24]. Briefly, RBCs were separated from whole blood, washed x3 with phosphate-buffered saline (PBS, Invitrogen, Carlsbad, CA), and centrifuged at 700 g for 5min at 4°C.…”
Section: Methodsmentioning
confidence: 99%
“…Most early studies have been focused on antibody-mediated destruction/rejection of xenogeneic RBCs, which involve complement-mediated cytotoxicity and antibody-dependent cellular cytotoxicity (ADCC). A recent study showed that RBCs from α1,3GalT KO pigs are significantly less susceptible than those from wild-type pigs to antibody-dependent complement-mediated cytotoxicity and ADCC by human macrophages [38], indicating that α1,3Gal is an important antigen causing destruction of porcine RBCs. However, depletion of α1,3Gal is not enough to overcome rejection, and α1,3GalT KO porcine RBCs were still rapidly and vigorously rejected after infusion into baboons [39].…”
Section: Macrophages In the Rejection Of Xenogeneic Red Blood Cellsmentioning
confidence: 99%
“…The number of migrated monocytes was assessed using a 96-well monocyte cell migration assay (EMD Millipore, San Diego, CA) based on the Boyen-chamber principle. Human monocytes were isolated from PBMCs, using monocyte isolation kit II (Miltenyl Biotec, Auburn, CA) as previously described 41 . Supernatants obtained from pCECs culture with/without Y27632 after hTNF-α stimulation were collected, and used in the monocytes migration assay.…”
Section: Methodsmentioning
confidence: 99%